Method for transfer growth of high-density vertical carbon nanotube-diamond composite material
By growing high-density VCNTs on Si substrates and growing continuous diamond films on VCNT-Si composites, the problem of difficult preparation of VCNTs on diamond substrates in the prior art is solved, and the preparation of high-density and strongly connected VCNT-diamond composites is realized, improving its heat transfer and light absorption performance.
Patent Information
- Application Number
- CN202411862463.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The prior art is difficult to prepare high-density, strongly connected vertical carbon nanotubes (VCNT) arrays on diamond substrates, resulting in failure of the ultra-black coating of VCNTs.
By growing high-density VCNT on the Si substrate, and then nucleation liquid is applied multiple times on the substrate surface of the VCNT-Si composite, the continuous diamond film is grown using CVD technology. The adhesion of VCNT on the diamond substrate is better than the adhesion performance on the Si substrate, the Si and VCNT-diamond composite material are separated, and the excess metal catalyst on the surface is removed to obtain a fully carbon VCNT-diamond composite material.
The preparation of high-density and strongly connected VCNT-diamond composite materials is achieved, which improves the heat transfer and light absorption performance of VCNT-diamond and reduces the risk of composite failure.
Smart Images

Figure CN119876893A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional material and device manufacturing, and relates to a method for transfer-growing a high-density vertical carbon nanotube-diamond composite material. Background Art
[0002] Infrared remote sensing technology has a wide range of applications in weather forecasting, climate monitoring, disaster prevention and mitigation, etc. Among them, infrared remote sensing radiation calibration is the core of the device, and rapid calibration requires the addition of ultra-black material components. Ultra-black materials have a strong ability to eliminate stray light, so they are visually beautiful. Moreover, as functional devices continue to develop in the direction of high precision and high efficiency, on the one hand, ultra-black coating materials are required to expand the spectral response band to a wide band, so as to achieve ideal absorption of the entire spectrum from ultraviolet, visible to far infrared; on the other hand, higher requirements are also put forward for the strong connection of the interface and heat transfer efficiency.
[0003] Vertical carbon nanotubes (VCNT) have a unique one-dimensional structure and a huge aspect ratio. They have high thermal conductivity (3000-3500 W / m·K) and ultra-high light absorption properties (ultra-high light absorption properties in the 0.25-16μm wide band, up to 99% or more), and are currently one of the "blackest" light-absorbing materials. Generally, high-density VCNT tubes are easy to prepare on Si-based substrates, but due to the weak adhesion between VCNT and Si substrate, they are prone to fall off, resulting in an enhanced heat accumulation effect at the carbon interface, causing the ultra-black coating of VCNT to fail. Diamond has high chemical stability and high thermal conductivity, and is an allotrope of carbon like VCNT. The VCNT array and the diamond substrate can form a strong chemical bond at the interface, thereby greatly improving the adhesion between VCNT and the diamond substrate.
[0004] Chinese patent CN 112981364 B grows VCNT on a diamond substrate for use in the optical field. However, due to the interaction between the diamond substrate and the catalyst, the quality of VCNT grown directly on the diamond surface is significantly different from that of VCNT grown on the silicon substrate surface. The high density of VCNT on the diamond substrate, the strong connection between VCNT and diamond, and the excellent heat transfer potential of the interface have not been fully utilized.
[0005] Therefore, it is of great application value to explore a method for fully carbon-based VCNTs that can achieve high-density preparation while also satisfying the requirement of strong interface bonding with diamond substrates. Summary of the invention
[0006] The technical problem to be solved by the present invention is to strengthen the interface between vertical carbon nanotubes (VCNT) and diamond, thereby realizing the preparation of strongly connected, high-density, large-size VCNT-diamond composite samples, which helps to improve the thermal transmission and light absorption properties of VCNT-diamond and reduce the risk of failure of the composite material.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0008] A method for transfer growth of high-density vertical carbon nanotube-diamond composite material, which realizes the composite of diamond film and high-density, large-area array VCNT. The method includes: first, growing high-density VCNT on the surface of Si substrate; then coating the surface of VCNT-Si composite substrate with nucleation liquid for many times; using CVD technology, gradually growing a continuous diamond film on the surface of VCNT-Si; using the adhesion of VCNT on diamond substrate to be better than that on Si substrate, separating Si and VCNT-diamond composite material; finally removing excess metal catalyst on the surface of VCNT-diamond composite material to obtain full-carbon VCNT-diamond composite material.
[0009] Furthermore, the method comprises the following steps:
[0010] S1. Preparation of VCNT-Si
[0011] To grow VCNT on a Si substrate, a discontinuous catalyst layer is first deposited on the cleaned Si substrate using radio frequency magnetron sputtering; then, the Si substrate is annealed in a CVD device to convert the discontinuous catalyst layer into nano-catalyst particles; finally, the CVD device is used again to grow VCNT on the surface of the Si substrate containing the catalyst particles.
[0012] Preferably, the catalyst is Fe, Ni, Fe x Ni y One of the catalyst layers has a thickness of 3~15 nm.
[0013] Preferably, the RF magnetron sputtering parameters are: vacuum is 2.0×10 -4 ~5.0×10 -4 Pa, the ambient temperature of the Si substrate is room temperature, the Ar flow rate is 40~70 sccm, and the sputtering power is 50~100 W.
[0014] Preferably, the CVD equipment is selected from one of microwave plasma chemical vapor deposition (MPCVD), plasma enhanced chemical vapor deposition (PECVD), and thermal CVD (TCVD).
[0015] Preferably, the annealing treatment parameters are: H2 flow rate is 200-300 sccm, maintained at a temperature of 500-700°C for 1-3 min, and then annealed for 5-20 min, so that the discontinuous catalyst layer on the Si surface is converted into nano catalyst particles.
[0016] Preferably, the parameters for growing VCNT on the surface of Si substrate using CVD equipment are: CH4 flow rate is 20-100 sccm, H2 flow rate is 50-300 sccm, deposition temperature is 450-700°C, deposition time is 20-120 min, and VCNT-Si composite material is obtained.
[0017] Preferably, the VCNT has a length of 50 to 300 μm.
[0018] S2, VCNT-Si surface coated with diamond nucleation liquid
[0019] First, in order to avoid the influence of metal catalysts on the growth of diamond film, the surface of the VCNT-Si composite material obtained in step S1 is pickled to remove excess metal catalysts, and then rinsed and dried with deionized water; in order to prevent hydrogen plasma from etching VCNT during the growth of diamond film, a hydroxyl-containing nanodiamond-carbon nanotube nucleation liquid is prepared, and the hydroxyl-containing nanodiamond-carbon nanotube nucleation liquid is spin-coated on the VCNT-Si surface and vacuum dried.
[0020] Preferably, the hydroxy-containing nano-diamond-carbon nanotube nucleation liquid is prepared by the following method: nano-diamond powder is placed in a mixed acid and boiled for 1h, wherein the mixed acid is obtained by mixing a volume of concentrated nitric acid of V1 and a volume of concentrated sulfuric acid of V2, wherein the mass concentration of concentrated nitric acid is 68%, the mass concentration of concentrated sulfuric acid is 98%, and V1:V2 = 1:3. The excess acid is then removed by ultrasonic cleaning in flowing deionized water, and finally dried to obtain hydroxy-containing nano-diamond. To prevent the occurrence of uneven nucleation, 1 mg of commercial hydroxylated multi-walled carbon nanotubes (MWCNT / OH, purity 99%) and 9 mg of hydroxy-containing nano-diamond are placed in a 500 mL ethanol solution, ultrasonically stirred for 1h, and a composite nucleation liquid of hydroxy-containing carbon nanotubes adsorbing nano-diamonds is obtained.
[0021] Preferably, the amount of nucleation liquid used in the surface spin coating is 3-5 mL; the spin coating speed is 300-500 rpm, and the spin coating time is 10-30 s. Repeat the above operation 3-5 times to form a dense nanodiamond and CNT protective layer on the VCNT surface.
[0022] S3, Diamond Nucleation
[0023] The VCNT-Si coated with the nucleation liquid obtained in S2 is placed in a CVD device to perform diamond nucleation on its surface.
[0024] Preferably, the diamond nucleation parameters are: nucleation temperature of 750-850° C., H2 flow rate of 200-300 sccm, CH4 flow rate of 30-50 sccm, and nucleation time of 5-20 min.
[0025] S4. Growth of diamond free-standing films
[0026] Diamond growth continues on the surface of one side of the VCNT-Si coated with the nucleation liquid until a diamond self-supporting film of a certain thickness is formed on the top of the carbon nanotube.
[0027] Preferably, the CVD is MPCVD or HFCVD.
[0028] Preferably, the diamond growth parameters are: deposition temperature of 700-800°C, H2 flow rate of 200-300 sccm, CH4 flow rate of 5-10 sccm, and growth time of 100-200 h.
[0029] Preferably, the self-supporting film has a thickness of 100 to 500 μm.
[0030] S5. Obtaining VCNT-diamond composite material
[0031] The Si substrate and the VCNT-diamond composite material in the VCNT-Si with diamond self-supporting film obtained in S4 were peeled off by mechanical separation, and the metal catalyst on the surface of the VCNT-diamond composite material was washed away with dilute acid, and then rinsed with flowing deionized water and vacuum dried to obtain a full-carbon VCNT-diamond composite material.
[0032] Preferably, the dilute acid is dilute hydrochloric acid or dilute sulfuric acid, with a mass concentration of 5 to 10%.
[0033] Preferably, the vacuum drying is carried out at a temperature of 90 to 120° C. and lasts for 20 to 40 minutes.
[0034] The present invention also provides a high-density vertical carbon nanotube-diamond composite material prepared by the method, and application of the material in the field of light absorption.
[0035] The present invention has the following beneficial effects:
[0036] It is impossible to prepare a high-density CNT array directly on the surface of a diamond substrate using the prior art. Since the surface of a silicon substrate is easy to grow CNT, the present invention first prepares a VCNT-Si composite material, and then connects the top of the carbon nanotube to the diamond substrate by using a nucleation liquid. Since the carbon nanotube is a hydrophobic / alcohol-phobic substance, during the spin coating process, the hydrophilicity of the carbon nanotube and the mixed nucleation liquid determines the uniformity of seeding on the surface of the carbon nanotube (the carbon nanotube grown on the surface of the silicon substrate). The carbon nanotube is added to the composite nucleation liquid to adsorb the modified nano-diamond particles to increase the uniformity of seeding. The cyclic process of seeding and nucleation can prevent the carbon nanotubes on the surface of the Si substrate from being etched by hydrogen ions, and also provides growth conditions for the growth of a self-supporting diamond film.
[0037] Then, the silicon substrate and VCNT-diamond composite material are directly separated by taking advantage of the fact that the adhesion between CNT and silicon is smaller than that between CNT and diamond, and an interface-reinforced high-density carbon nanotube-diamond composite material is obtained. This material has the characteristics of high heat dissipation, excellent light absorption, and high density. At the same time, the interface between VCNT and diamond is an embedded all-carbon interface connection with advantages such as high adhesion, providing a new type of alternative material for thermal and optical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0039] Figure 1 The figure is a flow chart of the preparation of the VCNT-diamond composite material of the present invention.
[0040] Figure 2 This is a SEM image of the diamond-VCNT-Si composite material obtained in step 5) of Example 1.
[0041] Figure 3 These are pictures of the composite materials subjected to ultrasonic oscillation for 5 hours, where (a) is the picture of the VCNT-diamond composite material before ultrasonic oscillation, (b) is the picture of the VCNT-diamond composite material after ultrasonic oscillation, (c) is the picture of the VCNT-Si before ultrasonic oscillation, and (d) is the picture of the VCNT-Si after ultrasonic oscillation.
[0042] Figure 4 The light absorption properties of the VCNT-composite material obtained in Example 1, wherein (a) is the light absorption property in the ultraviolet band, and (b) is the light absorption property in the infrared band.
[0043] Figure 5The light absorption properties of the VCNT-composite material obtained in Comparative Example 1, wherein (a) is the light absorption property in the ultraviolet band, and (b) is the light absorption property in the infrared band. DETAILED DESCRIPTION
[0044] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0045] Example 1
[0046] 1) Place the cleaned Si substrate into the RF magnetron device and evacuate the chamber to 3.0×10 -4 Pa, the substrate was 250 °C, and then Ar was passed through 70 sccm until the chamber pressure reached 3.6×10 -1 Pa, sputtering power 80 W, self-bias 270 V, voltage 1000 V, current 210 mA, bias 100 V, duty cycle 50%, frequency 42 Hz, Fe plating on the Si surface lasts for 1 min to the required film thickness of 6 nm (the film is discontinuous and there are gaps).
[0047] 2) Use MPCVD to nano-treat the Fe film on the Si surface. First, introduce 200 sccm of H2, the chamber pressure is 3 kPa, the temperature is raised to 650°C, the temperature is kept for 1 min, and annealing is performed for 8 min to obtain Fe catalyst particles. In order to grow VCNTs, the temperature is raised to 600°C, 180 sccm of H2 and 20 sccm of CH4 are introduced at a chamber pressure of 3 kPa for 60 min, and VCNTs are grown on the Si surface to obtain a VCNT-Si composite material with a VCNT length of 220 μm.
[0048] 3) To prevent the influence of metal catalyst on diamond quality, the VCNT-Si was turned upside down so that only the top surface of the VCNTs was exposed to dilute hydrochloric acid to remove the Fe catalyst particles on the surface of the VCNTs. The turned-up VCNT-Si was then exposed to flowing deionized water to remove excess Fe ions and dilute hydrochloric acid on the surface of the VCNTs, and then dried in a vacuum oven at 100°C for 30 minutes.
[0049] 4) The nano-diamond powder was placed in a mixed acid of concentrated nitric acid with a volume of V1 and concentrated sulfuric acid with a volume of V2 (the mass concentration of concentrated nitric acid was 68%, the mass concentration of concentrated sulfuric acid was 98%, V1: V2 = 1: 3) and boiled for 1 hour, then ultrasonically cleaned in flowing deionized water to remove excess acid, and finally dried to obtain hydroxyl nano-diamonds. To prevent the occurrence of uneven nucleation, 1 mg of commercial hydroxylated multi-walled carbon nanotubes (MWCNT / OH, purity 99%) and 9 mg of hydroxyl-containing nano-diamonds were placed in 500 mL of ethanol solution, ultrasonically stirred for 1 hour, and a composite nucleation solution of hydroxyl-containing carbon nanotubes adsorbing nano-diamonds was obtained. Subsequently, 3 mL of the composite nucleation solution was dropped on the surface of VCNT-Si and spin-coated, first at 300 rpm for 5 seconds, and then at 500 rpm for 60 seconds. Next, after heating at 110°C in a vacuum oven for 25 minutes, the VCNT-Si was placed in the MPCVD chamber, and 250sccm H2 and 50sccm CH4 were introduced into the chamber at 800°C for 10 minutes for diamond nucleation. The spin coating composite nucleation liquid-CVD nucleation process was repeated 8 times, and then dried in a vacuum oven at 110°C for 35 minutes.
[0050] 5) After the eighth diamond nucleation, the flow rate of CH4 was reduced from 50 sccm to 5 sccm, the temperature was 750°C, the growth time was 120 h, and the diamond film thickness was 150 μm;
[0051] 6) Finally, tweezers were used to fix the Si substrate and the diamond substrate respectively and to separate Si and VCNT-diamond, and dilute hydrochloric acid with a mass concentration of 15% was used to wash away the metal catalyst on the surface of VCNT-diamond. The Fe ions and excess dilute hydrochloric acid remaining on the surface of VCNT-diamond were rinsed with flowing deionized water, and then the VCNT-diamond was vacuum dried at 110°C for 20 minutes to finally obtain a full-carbon VCNT-diamond composite material.
[0052] Figure 1 The present invention is a flow chart for preparing the VCNT-diamond composite material. The present invention first deposits a catalyst on the surface of a Si substrate, grows VCNT on the side with the catalyst, and then removes the catalyst by pickling. A hydroxyl-containing nanodiamond-carbon nanotube nucleation liquid is coated on the side of the VCNT away from the silicon substrate, and then diamond nucleation is performed on the surface to grow a diamond self-supporting film. The Si substrate and the VCNT-diamond composite material are peeled off using a mechanical separation method to obtain the VCNT-diamond composite material.
[0053] Figure 2This is a SEM image of the diamond-VCNT-Si composite material obtained in step 5) of Example 1. This figure can ensure the authenticity of the example, and it can be seen that one side of the VCNT is a diamond self-supporting film and the other side is a silicon substrate. The diamond self-supporting film formed by CVD can be used as a high thermal conductivity diamond substrate to convert the radiation absorption of the vertical carbon nanotubes into heat and quickly conduct it away, and solve the problem of temperature calibration failure caused by the interface heat accumulation effect.
[0054] Figure 3 The following are pictures of composite materials after ultrasonic oscillation for 5 hours. The upper half of each small picture is a macroscopic picture taken by a digital camera, and the lower half is a SEM picture. The purpose is to detect the adhesion of VCNT on the substrate surface. Among them, (a) is a picture of VCNT-diamond composite material before ultrasonic oscillation, and it can be seen that VCNT is neatly distributed on the diamond surface; (b) is a picture of VCNT-diamond composite material after ultrasonic oscillation, and it can be seen that VCNT is partially tilted, but still exists on the diamond surface; (c) is a picture of VCNT-Si before ultrasonic oscillation, and it can be seen that the distribution of VCNT on the silicon substrate surface is the same as that in Figure (a); (d) is a picture of VCNT-Si after ultrasonic oscillation, and it can be seen that there are almost no carbon nanotubes distributed on the silicon substrate surface. Comparing Figures (a) to (d), it can be seen that the adhesion of carbon nanotubes on diamond substrates is much greater than that on silicon substrates. Ultrasonic oscillation can remove most of the carbon nanotubes on the silicon substrate surface, but cannot remove the carbon nanotubes on the diamond surface. In the embodiment, tweezers are used to directly separate silicon and carbon nanotube-diamond composite materials for auxiliary proof.
[0055] Figure 4 The light absorption performance of the VCNT-composite material obtained in Example 1, wherein (a) is the light absorption performance in the ultraviolet band, and (b) is the light absorption performance in the infrared band. It is shown that the absorption value of the material in the ultraviolet band of 0.25-2.5μm and the infrared band of 2.5-16μm is 99%. It can be used in infrared optical thermal imagers, and can also be used as a plane standard radiator to provide calibration thermal imagers. Due to the influence of infrared stray radiation, the image contrast and temperature indication accuracy of the thermal imager tend to decrease, and because the source of stray radiation in various cases is different, it is difficult to correct by pre-calibration. Therefore, the ultra-black VCNT-diamond composite material will provide accurate thermal imaging, including FTIR microscopy, fever screening, environmental remote sensing and infrared telescopes to detect highly redshifted early universe stars or exoplanet atmospheres. In addition, the infrared emissivity of the film will be maximized to increase the light power emitted by the light source at a given temperature. The ultra-black VCNT-diamond composite material has the potential for aerospace applications, can effectively transfer heat by radiation, and has a coating with high infrared emissivity to ensure the accuracy of temperature calibration.
[0056] Example 2
[0057] 1) Place the cleaned Si substrate into the RF magnetron device and evacuate the chamber to 3.0×10 -4 Pa, the substrate was 220 °C, and then Ar was passed through 40 sccm gas until the chamber pressure was 1.6×10 -1 Pa, sputtering power of 65 W, self-bias of 250 V, voltage of 950 V, current of 200 mA, bias of 100 V, duty cycle of 50%, frequency of 42 Hz, Ni plating on the Si surface lasts for 1.5 min to the required film thickness of 10 nm (the film is discontinuous and there are gaps).
[0058] 2) TCVD was used to nano-treat the Ni film on the Si surface. First, 300 sccm of H2 was introduced, the chamber pressure was 600 Pa, the temperature was raised to 700°C, the temperature was kept for 1 min, and annealing was performed for 10 min to obtain Ni catalyst particles. In order to grow VCNTs, the temperature was raised to 680°C, 200 sccm of H2, 100 sccm of CH4, the chamber pressure was 600 Pa, and it lasted for 100 min. VCNTs with a length of 200 μm were grown on the Si surface to obtain VCNT-Si composite materials.
[0059] 3) To prevent the influence of metal catalyst on diamond quality, the VCNT-Si was reversed to allow only the top surface of the VCNTs to contact dilute sulfuric acid to remove the Ni catalyst particles on the surface of the VCNTs. The reversed VCNT-Si was then placed in contact with flowing deionized water to remove excess Ni ions and dilute sulfuric acid on the surface of the VCNTs, and then dried in a vacuum oven at 110°C for 20 minutes.
[0060] 4) The nano-diamond powder was placed in a mixed acid of concentrated nitric acid with a volume of V1 and concentrated sulfuric acid with a volume of V2 (the mass concentration of concentrated nitric acid was 68%, the mass concentration of concentrated sulfuric acid was 98%, V1: V2 = 1: 3) and boiled for 1 hour, then ultrasonically cleaned in flowing deionized water to remove excess acid, and finally dried to obtain hydroxyl nano-diamonds. To prevent the occurrence of uneven nucleation, 1 mg of commercial hydroxylated multi-walled carbon nanotubes (MWCNT / OH, purity 99%) and 9 mg of hydroxyl-containing nano-diamonds were placed in 500 mL of ethanol solution, ultrasonically stirred for 1 hour, and a composite nucleation solution of hydroxyl-containing carbon nanotubes adsorbing nano-diamonds was obtained. Subsequently, 5 mL of the composite nucleation solution was dripped on the top surface of VCNTs for spin coating, first at 350 rpm for 5 seconds, and then at 400 rpm for 60 seconds. After heating at 100°C in a vacuum oven for 30 min, the VCNT-Si was placed in the HFCVD chamber, and 250 sccm H2 and 50 sccm CH4 were introduced into the chamber at 820°C for 15 min for diamond nucleation. The spin coating composite nucleation liquid-diamond nucleation process was repeated 10 times.
[0061] 5) After the 10th diamond nucleation, the flow rate of CH4 was reduced from 50sccm to 10sccm, the temperature was 800℃, the growth time was 110 h, and the diamond film thickness was 170 μm;
[0062] Finally, tweezers were used to fix the Si substrate and diamond substrate and separate Si and VCNT-diamond, and the metal catalyst on the surface of VCNT-diamond was washed away with dilute sulfuric acid with a mass concentration of 10%, and the Ni ions and excess dilute sulfuric acid remaining on the surface of VCNT-diamond were washed with flowing deionized water, and then the VCNT diamond was vacuum dried at 105℃ for 25 minutes to finally obtain a full-carbon VCNT-diamond composite material. The light absorption performance was tested in the infrared and ultraviolet bands, and the absorption values were all 99%.
[0063] Comparative Example 1
[0064] 1) Place the cleaned Si substrate into the RF magnetron device and evacuate the chamber to 3.0×10 -4 Pa, the substrate was 220 °C, and then Ar was passed through 40 sccm gas until the chamber pressure was 1.6×10 -1 Pa, sputtering power 65 W, self bias 250 V, voltage 950 V, current 200 mA, bias 100 V, duty cycle 50%, frequency 42 Hz, Fe is plated on Si surface x Ni y Continue for 2 min until the desired film thickness is 11 nm (the film is discontinuous and has gaps).
[0065] 2) Using TCVD to deposit Fe on Si surface x Ni y The film was nano-processed by introducing 300 sccm of H2, the chamber pressure was 600Pa, the temperature was raised to 700℃, the temperature was kept for 1 min, and annealed for 10 min to obtain Fe x Ni y Catalyst particles. In order to grow VCNTs, the temperature was raised to 680°C and 200 sccm of H2, 100 sccm of CH4, and the chamber pressure was 600 Pa for 100 min. VCNTs were grown on the Si surface with a length of 200 μm to obtain a VCNT-Si composite material.
[0066] 3) To prevent the metal catalyst from affecting the quality of diamond, the VCNT-Si was reversed to allow only the top surface of the VCNTs to contact the dilute sulfuric acid to remove the Ni catalyst particles on the surface of the VCNTs. The reversed VCNT-Si was then placed in contact with flowing deionized water to remove the excess Fe Ni ions and dilute sulfuric acid and dried in a vacuum oven at 100 °C for 25 min.
[0067] 4) Place the nano-diamond powder in a mixed acid of concentrated nitric acid (V1: V2 = 1: 3) with a volume of V1 and concentrated sulfuric acid (V2) and boil for 1 hour, then ultrasonically clean in flowing deionized water to remove excess acid, and finally dry to obtain hydroxyl nano-diamond. Then, 9 mg of hydroxyl-containing nano-diamond is placed in a 500 mL ethanol solution, ultrasonically stirred for 1 hour, and a composite nucleation liquid containing hydroxyl carbon nanotubes adsorbing nano-diamonds is obtained. 5 mL of hydroxyl nano-diamond nucleation liquid is dripped onto the top surface of VCNTs for spin coating, first at 350 rpm for 5 seconds, then at 400 rpm for 60 seconds. After heating at 100 ° C in a vacuum drying oven for 30 minutes, the VCNT-Si is placed in the HFCVD chamber, and 250 sccm H2 and 50 sccm CH4 are introduced into the chamber at 820 ° C for 15 minutes for diamond nucleation. Repeat the spin coating nucleation liquid-diamond nucleation process 10 times.
[0068] 5) After the 10th diamond nucleation, the flow rate of CH4 was reduced from 50sccm to 10sccm, the temperature was 800℃, the growth time was 110 h, and the diamond film thickness was 170 μm;
[0069] Finally, tweezers were used to fix the Si substrate and the diamond substrate respectively and to separate the Si and VCNT-diamond, and dilute sulfuric acid was used to wash away the metal catalyst on the surface of the VCNT-diamond. Flowing deionized water was used to rinse the Ni ions and excess dilute sulfuric acid remaining on the surface of the VCNT-diamond. The VCNT-diamond was then vacuum dried at 105°C for 25 minutes to finally obtain a full-carbon VCNT-diamond composite material.
[0070] Figure 5 (a) and Figure 5 (b) are the ultraviolet and infrared absorption spectra of the comparative VCNT-diamond composite material, respectively. Its ultraviolet absorption maximum is only 5%, and its infrared absorption maximum is 80% and unstable. The reason is that no commercial hydroxy carbon nanotube solution is added during the nucleation process, which makes the nanodiamond unevenly distributed during the spin coating process. During the nucleation process and the process of growing diamond, the carbon nanotubes on the surface of the CNT-Si composite substrate are etched by hydrogen plasma, resulting in a very uneven distribution of carbon nanotubes on the diamond surface, and a sharp drop in the ultraviolet-infrared absorption performance.
[0071] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for transfer growth of high-density vertical carbon nanotube-diamond composite materials, characterized in that: The method comprises: Growing high-density VCNTs on the surface of Si substrate; Nucleation liquid is coated on the surface of the VCNT-Si composite material substrate multiple times; Using CVD technology, a continuous diamond film is gradually grown on the surface of VCNT-Si; Taking advantage of the fact that VCNT has better adhesion on diamond substrate than on Si substrate, Si and VCNT-diamond composite materials are separated; The excess metal catalyst on the surface of the VCNT-diamond composite material is removed to obtain a full-carbon VCNT-diamond composite material.
2. A method for transfer growth of high-density vertical carbon nanotube-diamond composite material, characterized in that: The method comprises the following steps: S1. Preparation of VCNT-Si First, a discontinuous catalyst layer is deposited on a cleaned Si substrate using radio frequency magnetron sputtering; then the Si substrate is annealed in a CVD device to convert the discontinuous catalyst layer into nano-catalyst particles; finally, CVD equipment is used again to grow VCNT on the surface of the Si substrate containing the catalyst particles; S2, VCNT-Si surface coated with diamond nucleation liquid The surface of the VCNT-Si composite material obtained in step S1 is pickled, and then a hydroxyl-containing nanodiamond-carbon nanotube nucleation liquid is spin-coated on the surface of the VCNT-Si and vacuum dried; S3, Diamond Nucleation The VCNT-Si coated with the nucleation liquid obtained in S2 is placed in a CVD device to perform diamond nucleation on its surface; S4. Growth of diamond free-standing films Diamond growth continues on the surface of one side of the VCNT-Si coated with the nucleation liquid until a diamond self-supporting film is formed on the top of the carbon nanotube; S5. Obtaining VCNT-diamond composite material The Si substrate and the VCNT-diamond composite material in the VCNT-Si with diamond self-supporting film obtained in S4 were peeled off by mechanical separation, and the metal catalyst on the surface of the VCNT-diamond composite material was washed away with dilute acid, and then rinsed with flowing deionized water and vacuum dried to obtain a full-carbon VCNT-diamond composite material.
3. The method for transfer growth of high-density vertical carbon nanotube-diamond composite material according to claim 2, characterized in that: In step S1, the catalyst is Fe, Ni, Fe x Ni y One of the catalyst layers has a thickness of 3~15 nm.
4. The method for transfer growth of high-density vertical carbon nanotube-diamond composite material according to claim 2, characterized in that: In step S1, the RF magnetron sputtering parameters are: vacuum is 2.0×10 -4 ~5.0×10 -4 Pa, the ambient temperature of the Si substrate is room temperature, the Ar flow rate is 40~70 sccm, and the sputtering power is 50~100 W; And / or, the annealing treatment parameters are: H2 flow rate is 200-300 sccm, maintained at a temperature of 500-700°C for 1-3 min, and then annealed for 5-20 min, so that the discontinuous catalyst layer on the Si surface is converted into nano catalyst particles; And / or, the parameters of growing VCNT on the surface of Si substrate using CVD equipment are: CH4 flow rate is 20-100 sccm, H2 flow rate is 50-300 sccm, deposition temperature is 450-700°C, deposition time is 20-120 min, to obtain VCNT-Si composite material; And / or, the VCNT has a length of 50 to 300 μm.
5. The method for transfer growth of high-density vertical carbon nanotube-diamond composite material according to claim 2, characterized in that: In step S2, the hydroxyl-containing nanodiamond-carbon nanotube nucleation liquid is prepared by the following method: The nano-diamond powder is placed in a mixed acid and boiled for 1 hour. The mixed acid is obtained by mixing concentrated nitric acid with a volume of V1 and concentrated sulfuric acid with a volume of V2. The mass concentration of the concentrated nitric acid is 68%, the mass concentration of the concentrated sulfuric acid is 98%, and V1:V2 = 1:
3. The excess acid is then removed by ultrasonic cleaning in flowing deionized water, and the nano-diamond containing hydroxyl groups is dried. 1 mg of commercial hydroxylated multi-walled carbon nanotubes and 9 mg of hydroxyl-containing nanodiamonds were placed in 500 mL of ethanol solution, ultrasonicated and stirred for 1 hour to obtain a composite nucleation solution in which hydroxyl-containing carbon nanotubes adsorbed nanodiamonds.
6. The method for transfer growth of high-density vertical carbon nanotube-diamond composite material according to claim 2, characterized in that: In step S2, the amount of nucleation liquid used for the surface spin coating is 3-5 mL; the spin coating speed is 300-500 rpm, and the spin coating time is 10-30 s; the above operation is repeated 3-5 times to form a dense nano-diamond and CNT protective layer on the VCNT surface.
7. The method for transfer growth of high-density vertical carbon nanotube-diamond composite material according to claim 2, characterized in that: In step S3, the diamond nucleation parameters are: nucleation temperature is 750-850°C, H2 flow rate is 200-300 sccm, CH4 flow rate is 30-50 sccm, and nucleation time is 5-20 min.
8. The method for transfer growth of high-density vertical carbon nanotube-diamond composite material according to claim 2, characterized in that: In step S4, the diamond growth parameters are: deposition temperature of 700-800°C, H2 flow rate of 200-300 sccm, CH4 flow rate of 5-10 sccm, and growth time of 100-200 h; And / or, the self-supporting film has a thickness of 100 to 500 μm.
9. A high-density vertical carbon nanotube-diamond composite material prepared by the method according to any one of claims 1 to 8.
10. Application of the high-density vertical carbon nanotube-diamond composite material according to claim 9 in the field of light absorption.
Citation Information
Patent Citations
A fast-response superblack material and its preparation method
CN112981364B
Vertical carbon nanotube array / diamond-like carbon film composite adhesion material, preparation method and application
CN116925692A
Preparation method of interface material for enhancing radiation heat dissipation of high-power electronic device
CN118621294A
Preparation of perpendicularly oriented carbon nanotube
JP2001048512A
Method for producing single layer carbon nanotube-containing composition
JP2018016521A